2002
DOI: 10.1161/01.str.0000013671.70986.39
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke, Transient Ischemic Attack, and Vessel Occlusion Before Endarterectomy in Patients With Symptomatic Severe Carotid Stenosis

Abstract: Background and Purpose-We aimed to identify and determine the clinical relevance of parameters predictive of stroke recurrence and vessel occlusion before carotid endarterectomy. Methods-One hundred forty-three consecutive patients (105 men; mean age, 66.1Ϯ8 years) with symptomatic severe carotid artery stenosis were prospectively followed up until carotid endarterectomy. Patients had suffered an ischemic vascular event in the ipsilateral anterior circulation 9.6 days (median; range, 0 to 92 days) before prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
98
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(110 citation statements)
references
References 30 publications
6
98
0
6
Order By: Relevance
“…Past cross-sectional and prospective studies have indicated that the ultrasound-detected carotid atherosclerotic lesions were associated with ischemic stroke (1, 2) and coronary heart diseases (22,23), and that these lesions can help to estimate the risk of ischemic stroke (3)(4)(5)(6)(7)(8). Our study showed the two types of carotid lesion were related with SCI.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Past cross-sectional and prospective studies have indicated that the ultrasound-detected carotid atherosclerotic lesions were associated with ischemic stroke (1, 2) and coronary heart diseases (22,23), and that these lesions can help to estimate the risk of ischemic stroke (3)(4)(5)(6)(7)(8). Our study showed the two types of carotid lesion were related with SCI.…”
Section: Discussionsupporting
confidence: 52%
“…Increased intima-media thickness (IMT) and atherosclerotic plaques in the carotid arteries have been reported to have associations with ischemic stroke (1)(2)(3)(4)(5)(6)(7)(8), and therefore have been recognized as useful risk assessment tools for cerebrovascular diseases (9,10). Similarly, brachialankle pulse wave velocity (baPWV) has been investigated as a new method of assessing systemic atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, impaired CVR has been associated with risk for stroke and transient ischemic attacks (Liu et al, 2012;Zirak et al, 2014). Given similar diagnoses, individuals with CVR impairment have a much higher risk of disabling stroke than those without (Blaser et al, 2002;Bokkers et al, 2011;Kuroda et al, 2004;Mandell et al, 2011;Mandell et al, 2008;Markus and Cullinane, 2001;Schoof et al, 2007;Silvestrini et al, 2000 ;Tsivgoulis and Alexandrov, 2008). In addition, reduced CVR has also been cited as a marker for lacunar infarction (Birns et al, 2009;Mandell et al, 2011), microbleeding (Birns et al, 2009;Conijn et al, 2012), as well as cortical atrophy (Fierstra et al, 2010) and cognitive decline in individuals at risk of stroke (Hurford et al, 2014;Kovács et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…24 Also patients with symptomatic stenosis and ipsilateral hemodynamic compromise are at higher risk of disabling stroke than patients with normal cerebral perfusion. 4 It is important to evaluate individual perfusion parameters and relate these to the different stages of hemodynamic compromise. MTT is considered the most sensitive perfusion parameter because it directly relates to cerebral perfusion pres- The significance of the difference between relative perfusion parameters was tested using the paired-samples t test in symptomatic patients and the Wilcoxon signed rank test in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Collateral circulation, on the other hand, can maintain normal cerebral perfusion pressure and normal flow in many patients with carotid artery stenosis. 3 In symptomatic patients with severe carotid stenosis and occlusion, [4][5][6] the association of cerebral hemodynamics with the risk of stroke has been described. In asymptomatic patients with severe carotid stenosis, less proof of this association is available.…”
mentioning
confidence: 99%